EFFECT OF FAMILY INCOME, EDUCATION LEVEL AND FIRST MARRIED AGE ON FERTILITY IN LHOKSEUMAWE CITY (Case Study in Mns. Mesjid Muara Dua District, Lhokseumawe City) - Maqvirah Maqvirah; Ratna Ratna (LPPM Universitas Malikussaleh, 2018)
The purpose of this study is to see the effect of family income, edducation level and first marriage age on fertility in Meunasah. Muara Dua District, Lhokseumawe City. The data used in the study are primary data collectedd from 95 respondents. The data analysis used in this study is a multiple linear regression model. The resultsshow that family income positively influence fertility, while the edducation level and first marriage age negatvely affected fertility in the village of Meunasah. Masjid village Muara Dua District, Lhokseumawe city.